METHODOLOGICAL FOUNDATIONS FOR THE PREPARATION OF FUTURE CHEMISTRY TEACHERS FOR THE PROFESSION - Kamolova Nargiza; Turdiyev Zarif (Journals Park Publishing, 2024)
The purpose of this article is to study the knowledge of teachers in the field of chemical and technological science. Using new learning modules, new principles of computational chemistry for chemistry teachers are explored.
Keywords: chemistry, teacher, effective approach, scientific and methodological bases, vocational training, new modules, technological science, pedagogical science.